Education policy, student migration, and brain gain - Alexander Haupt; Tim Krieger; Thomas Lange (Albert-Ludwigs-Universität Freiburg, Wilfried-Guth-Stiftungsprofessur für Ordnungs- und Wettbewerbspolitik, 2013)
In this paper, we analyse how increasing student migration from a less developed to a developed country alters education policy in the developed country, and how it affects human capital and welfare in the two countries. We argue that a higher permanent migration probability, i.e., a higher probability that international students continue to stay in their host country after graduation, incentivises the host country to improve its education quality. A higher education quality in turn raises the human capital of all students, including returning students. As long as the permanent migration probability is not too large, this positive quality effect increases human capital and welfare in both the less developed country (LDC) and the developed host country. Thus, a brain gain to the LDC occurs. A decline in the taxes on labour income in the two countries can reinforce this brain gain, although the developed country then raises the tuition fees.
Keywords: F22; I28; H52; 330; brain gain; education; human capital; mobility; return migration